Multibeam bathymetry raw data (Kongsberg EM710 entire dataset) of RV SONNE during cruise SO292 - Sebastian Lindhorst; Jan Oliver Eisermann; Johanna Becking; Pauline Falkenberg; Joely Marie Maak; Victoria Christl Strehse; Christian Betzler; Mia Schumacher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV SONNE during cruise SO292 using a Kongsberg EM 710 multibeam echosounder. The expedition took place during 15.05.2022 – 21.06.2022 from Nouméa (New Caledonia) - Nouméa (New Caledonia) in the central Pacific Ocean. The main objective of SO292 was to analyse the sedimentology, the stratigraphy and the oceanography of the isolated carbonate platforms of the Queensland Plateau (NE Australia) within the ICECARB project. Data were recorded within the Australian EEZ. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data provision is part of the DAM Underway Project and published according to the FAIR principles.